80‐3: Design of Spatial Light Modulator on Glass using Oxide TFTs with Lower Off‐state Current. Issue 1 (May 2017) - Pi, Jae-Eun; Choi, Ji Hun; Hwang, Chi-Young; Yang, Jong-Heon; Cho, Sung Haeng; Kim, GiHeon; Kim, Yong-Hae; Kwon, Oh-Sang; Kim, Hee-Ok; Park, Eun-Suk; Hwang, Chi-Sun
Abstract : We designed the spatial light modulator (SLM) on a glass (SLMoG) for holographic display. The lower off current of the pixel switch TFT is important to realize small pixel pitch for ultra‐high PPI in display panel. A 2 um channel length ITZO TFT with low off current was used for a pixel switch TFT of SLMoG. We demonstrated 1.87 inch SLMoG panel with the pixel pitch of 7 um and 5760×1080 resolution.